2006
DOI: 10.1016/j.ccr.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signature-based chemical genomic prediction identifies a novel class of HSP90 pathway modulators

Abstract: Although androgen receptor (AR)-mediated signaling is central to prostate cancer, the ability to modulate AR signaling states is limited. Here we establish a chemical genomic approach for discovery and target prediction of modulators of cancer phenotypes, as exemplified by AR signaling. We first identify AR activation inhibitors, including a group of structurally related compounds comprising celastrol, gedunin, and derivatives. To develop an in silico approach for target pathway identification, we apply a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
551
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(573 citation statements)
references
References 46 publications
16
551
2
4
Order By: Relevance
“…Previous studies have shown that celastrol (Fig. 1A), a quinone methide triterpene from Tripterygium wilfordii Hook F regulated the Hsp90 pathway and induced the heat shock response similar to other Hsp90 inhibitors (12,13). We found that celastrol did not effect ATP binding to Hsp90.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Previous studies have shown that celastrol (Fig. 1A), a quinone methide triterpene from Tripterygium wilfordii Hook F regulated the Hsp90 pathway and induced the heat shock response similar to other Hsp90 inhibitors (12,13). We found that celastrol did not effect ATP binding to Hsp90.…”
Section: Introductionsupporting
confidence: 57%
“…However, celastrol did not interrupt the Hsp90-p23 complex in pancreatic cancer cells (Fig. 3A and B), although different results have been reported in SKBR-3 cells (13). The computer modeling also showed p23 blocked the access of celastrol to its binding site in the Hsp90/p23 complex (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…64 This multi-step study design first required identifying a molecular signature associated with androgen repression by using the hormone-sensitive LNCaP PCA cell line and comparing gene expression profiles with and without the presence of androgen. After identification of 27 AR genes associated with the androgen-repressed state, 65 a bead-based multiplex assay (Luminex Beads) was developed to identify which genes from approximately 2500 compounds produced the same expression signature in LNCaP cells as was originally observed by androgen deprivation.…”
Section: Novel Chemical Genomics Approaches To Identifying Regulatorsmentioning
confidence: 99%
“…16 High-throughput screening for androgen signalling inhibitors has identified Celastrol in blocking the interactions between HSP90 and co-chaperone Cdc37/p23. 17 Yang et al demonstrated the inhibitory effect of Celastrol on rabbit 20S proteasomes and elicited cell apoptosis in prostate cancer cells. 18 In addition, Celastrol treatment triggered heat shock response via inducing HSP70 expression.…”
Section: Introductionmentioning
confidence: 99%